Experimental, computational, and simulation methods for investigating the pore connectivity of cement-based materials: a review - Luo, Zhiyuan; Jiao, Libin (Frontiers in Materials, 2025)
Pore connectivity (β) is a key parameter for investigating the hydration mechanism, transport performance, corrosion mechanism, and durability of cement-based materials. This article reviews the general experimental and computational, and numerical simulation methods used to study the β of cement-based materials. The principles, characteristics, and application of traditional and advanced experimental methods used to study the β of cement-based materials are compared and analysed. The principles and research progress of computational models, including random walker algorithm, Archie’s law, and multi-phase phenomenological model, are summarised. The characteristics of numerical simulation methods, such as hydration-morphology-structure, CEMHYD3D, and HydratiCA, are described. Additionally, the research progress, challenges, and directions with respect to the β of cement-based materials are comprehensively discussed. This review aims to provide some foundation for understanding the pore structure, hydration and corrosion mechanism and for developing a durability prediction model of cement-based materials in the future.